1954
DOI: 10.1039/jr9540000923
|View full text |Cite
|
Sign up to set email alerts
|

Addition of free radicals to unsaturated systems. Part VII. 1 : 1-Difluoroethylene

Abstract: The photochemical reaction of trifluoroiodomethane with 1 : l-difluoroethylene yields only the compound CF,CH,*CF,I, i.e. , the trifluoromethyl radical attacks exclusively the :CH, group. Proof of constitution is given. Iodine monobromide and 1 : l-difluoroethylene yield only 1-bromo-1 : 1difluoro-2-iodoethane ; the iodo-compound is converted into 1 : 1 : 1-trifluoro-2-iodoethane by means of mercurous fluoride.THE direction of addition of a trifluoromethyl radical, derived from trifluoroiodomethane , to vinyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Indeed, high power UV photoinduced telomerizations were described for VDF over 50 years ago (19,77,78). Likewise, we have also confirmed (50,(79)(80)(81)(82) that VDF free radical polymerization (FRP) occurs readily under UV irradiation at rt in the presence of TBPO.…”
Section: Introductionsupporting
confidence: 78%
“…Indeed, high power UV photoinduced telomerizations were described for VDF over 50 years ago (19,77,78). Likewise, we have also confirmed (50,(79)(80)(81)(82) that VDF free radical polymerization (FRP) occurs readily under UV irradiation at rt in the presence of TBPO.…”
Section: Introductionsupporting
confidence: 78%
“…Few works on photoinitiation and different radical initiators have also been performed. [53][54][55] On the other hand, iodine transfer polymerization (ITP) of VDF with C 6 F 13 I, C 6 F 13 CH 2 CH 2 I or HCF 2 CF 2 CH 2 I, initiated by tert-butylperoxypivalate (TBPPi) has been reported, 56,57 but to our best knowledge no telomerization of VDF with (CF 3 ) 2 CFI has been initiated by TBPPi.…”
Section: R F -Vdf-i Telomersmentioning
confidence: 99%
“…Perfluoroalkyl iodides or a,v-diiodoperfluoroalkanes act as efficient chain transfer agents (CTA), since they easily undergo CF 2 -I bond cleavage [5,6,9,11,12,14,15,[20][21][22] leading to low molecular weight molecules. Most studies on the direction of addition of the telogen onto the asymmetric monomer (VDF) have shown that the addition mainly occurs onto the methylene groups of VDF [11,15,[20][21][22][23][24][25][26][27], and that it is regioselective.…”
Section: Introductionmentioning
confidence: 99%
“…The telomerization of vinylidene fluoride has been extensively investigated [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Perfluoroalkyl iodides or a,v-diiodoperfluoroalkanes act as efficient chain transfer agents (CTA), since they easily undergo CF 2 -I bond cleavage [5,6,9,11,12,14,15,[20][21][22] leading to low molecular weight molecules.…”
Section: Introductionmentioning
confidence: 99%